Case Report: Application of 18F-FDG PET/CT in identifying plasmacytoma in monoclonal gammopathy associated peripheral neuropathy - Weng, Jiequn; Lin, Jie; Sun, Chong (Frontiers in Nuclear Medicine, 2024)
Peripheral neuropathy is a prevalent complication in plasma cell disorders, posing significant diagnostic and therapeutic challenges. This study presents three cases initially diagnosed with chronic inflammatory demyelinating polyneuropathy (CIDP). Despite initial symptom regression post-immunomodulatory treatment, the patients exhibited progressive neurological deficits. Advanced laboratory evaluation confirmed monoclonal protein presence, yet traditional diagnostic methods, including bone marrow biopsy and flow cytometry, yielded normal results. Utilizing 18 F-FDG PET/CT, we identified multiple hypermetabolic vertebral lesions, which upon biopsy, confirmed the diagnosis of plasmacytoma. Our findings underscore the utility of PET/CT as a reliable diagnostic tool for monoclonal gammopathy associated neuropathy, advocating for its consideration in cases with equivocal diagnosis. When the diagnosis is in doubt, biopsy of a lesion may facilitate early and accurate diagnosis, potentially influencing treatment strategies and patient outcomes.